(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A key environmental issue is disposal of pozzolonic waste material such as fly ash, pond ash, coal ash, ground granulated blast furnace sag which can be used in civil engineering work such as road embankment, rail embankment, retaining wall, filling structures. This paper presents results of experimental investigation carried out to evaluate effect of fly ash on soft soil and its suitability as material for embankment. In this investigation, stabilized soil samples are prepared at different Class C fly ash content, i.e., 0, 10, 15, 20, 25, 30 and optimum proportion of fly ash with partial replacement of soft soil is found out. In experimental study, index properties of soft soil and fly ash stabilized soil samples are determined. The literature review clearly states that more than 30 replacement of soil with fly ash gives lower result in respect to unconfined strength and California Bearing test. As we increase of fly ash there is reduction in maximum dry density and optimum moisture content but with 20 fly ash gives best suited result of all proportions. The result of this research showed improved soil parameters such as swelling index reduced, specific gravity reduced, and permeability reduced.